Cavernous sinus fungal infection: a rare case - Ng, Kevin; Giat, Seng Kho; Sze, Kiat Sim; Liew, Donald Ngian San; Tang, Ing Ping (Taylor and Francis Ltd, 2017)
Intracranial fungal infection of the cavernous sinus is a condition that usually affects immunocompromised individuals and is rarely seen in immunocompetent individuals. It is a potentially life threatening condition which requires prompt treatment. Here we present a case of an immunocompetent patient with a fungal infection of the cavernous sinus.